PENGARUH DIVERSITAS DEWAN DIREKSI TERHADAP NILAI PERUSAHAAN - Refi Muhammad Syafei (2021)
This research aims to determine the impact of gender diversity, national diversity, educational diversity, and age diversity on the board of directors (including committee members and directors), and the impact on the firm value of 50 non-financial companies listed on the Indonesian stock exchange and based on the Kompas100 stock index during the period 2015-2019. This study is a quantitative study using secondary data in the form of company financials and annual reports. In this study, a fixed effects model (FEM) with panel data regression was used, using STATA version 16. Based on the results of testing and analysis, it can be concluded that gender diversity, nationality, education level, and age have no significant impact on c value and control variable, namely leverage, has a negative impact on firm value. Then the book-to-market ratio also has a negative impact on the firm value. However, company size has no effect on firm value.